(untitled) (Damascus University Journal of arts and humanities sciences, 2026)
Rational philosophy, which is classified under the name First Philosophy, is the space that provided us with human understanding of positive implications, especially since the “ego” is the mirror that presents itself as thought, where thought presents manifestations of a personal nature to form the essence of this “ego” and is the best guide. Thus, the Cogito struggles for the independence of the self from any concept of a phenomenal nature. In this research, we will attempt to present the essence of (the I think) within the work of interpretation according to (Paul Ricoeur) and to clarify the importance of (the cogito) within hermeneutics, especially since (Ricoeur) allowed us the rational philosophy of interpretation and presented it as a pure project within the trilogy of intellectual symbols in establishing intermediate interpretation first. Secondly, bypassing the process of matching the subject and the object, and reducing the idea of ​​accusation and direct claims towards the subject’s action. Therefore, we are carrying out this research to show the wounded cogito that will be subject to interpretation in identifying special mechanisms for thinking, and presenting it as one of these mechanisms. From here, Ricoeur builds the project of destroying the problem of the self as consciousness, in addition to devoting the “ego” as a primary source in interpreting the reality of contemplation, and the possibility of clarifying transparency. Clarity and distance from the ambiguity that falls under the category of symbols. So the cogito presented by Ricoeur is subjective possibilities in private thinking, and it is an inference about the existence of the conscious self, but on the other hand, it is an existential intuition based on defining identity and getting out of the sin that haunts the memory of the liberated person.